Influence Of Human Relations And Work Environment On Employee Performance At PT Perkebunan Nusantara IV Regional IV Kebun Rimbo Satu - Vinna Anggraini; Kelik Purwanto; Dini Elida Putri (Jurnal Ekonomi, 2024)
In an organisation there are many factors that affect employee performance. James (2014: 124) suggests ‘there are several factors that affect employee performance including leadership, motivation, work environment, compensation, organisational culture, job satisfaction, competence and work discipline’. So employees as much as possible solve their work problems, for maximum achievement there must be proper human relations. This study was conducted to determine and analyse what kind of influence human relations and work environment on employee performance at PT Perkebunan Nusantara IV Regional IV Kebun Rimbo Satu. The purpose of this study was to determine and analyse the effect of human relations and work environment on employee performance. The method of analysis in this study is to use quantitative methods with data collection using questionnaires. The type of data used in this study is primary data, the data collection method used is a questionnaire and processed using SPSS 20. Respondents who were sampled were employees of PTPN IV Region IV Kebun Rimbo Satu. Based on the T test shows that the human relations variable has no positive and significant effect on employee performance (1,360 < 1,668), while the work environment has a positive and significant effect on employee performance (2,466 > 1,668). Based on the coefficient of determination (R2) shows that human relations and the work environment have a positive effect and significant effect on employee performance.